A study on real estate market case: factors affecting housing price in Malaysia / Intan Zafina Abdul Manaf - Abdul Manaf, Intan Zafina (Faculty of Business and Management, 2011)
This study of “Factors Affecting Housing Price: A Case Study of Housing Price will concentrate on studying the relationship between Housing Price in Malaysia and some selected variables which comprises of inflation rate, Base Lending Rate and Economy growth (GDP). This study examines if there exists any significant relationship between the dependent variable and the independent variables.